Advancements In Blockchain Cryptography: Self-Signed Key Applications For Digital Record Protection - Pawan Maheshwari; Sunil Gupta (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
The significant deployment of Electronic Health Records (EHRs) has introduced serious issues with data security and confidentiality. The proposed study addresses such issues by investigating innovation in blockchain cryptography, with a special focus on the application of self-signed keys for secure digital record management. The research combines the use of Elliptic Curve Cryptography (ECC) with a blockchain framework to suggest a decentralized and efficient solution for the management and authentication of digital records. The experimental evaluation of the proposed solution indicates the efficiency of the system with 1626.03 seconds of execution time, 0.0018 tps of throughput, and 3.1790 seconds of the average latency for 1000 transactions. Furthermore, the proposed solution reduces the encryption time to 3650 ms and the decryption time to 3968 ms as compared to the traditional implementation of the blockchain, with ensured data integrity. The outcome attests to the practicability of the employment of the application of the self-signed keys for the improvement of security, confidentiality, and integrity of data for healthcare systems. Furthermore, the proposed solution strengthens decentralized systems with the introduction of the optimized mechanism of cryptography that maintains efficiency with the guarantee of security, introducing a practical mechanism for the protection of confidential medical data for real-world systems.